Oral history interview with Dimitris Korakis / Interviewee Korakis, Dimitris Date interview: 2014 November 12 Language Greek Extent 1 digital file : MPEG-4. Credit Line United States Holocaust Memorial Museum Collection, courtesy of the Jeff and Toby Herr Foundation (United States Holocaust Memorial Museum, 2014)
Interviewee Korakis, Dimitris Date interview: 2014 November 12 Language Greek Extent 1 digital file : MPEG-4. Credit Line United States Holocaust Memorial Museum Collection, courtesy of the Jeff and Toby Herr Foundation: ... ... ... ... ... ... ... Thank you very much for coming and meeting us again today, can you tell me your name? My name is Dimitrios Korakis, I was born in Ioannina in 1933, on the 5th of February. Mr. Korakis, in which area does your family live? When I was born, the family had already been created because I am the last child of the family. We lived in the great Alexandria, on the road above Bostania, which was from this road to the lake of Ioannina. How many members did your family have? We had 8 members, first of all we had 7 siblings, of which a girl and a boy had died. So we stayed with the 5 children, my parents, and we had Mrs. Manna in our house. Mrs. Manna was the mother of my mother, she was a maid, and she helped my mother in her work and raising the other 5 children. Did your family have any relations with the Jews? Very much, because my father had a vegetable garden in Bostania, which was close to the house we lived in, on this road. It was the house, and right across the street there was a narrow road that ended in Bostania. So my father sold the vegetables to a Jew, David. We all knew David, as well as another vegetable seller. So the relations with this family were very strong, but because the area there was in Kourmanio, there were also Jewish houses in the castle and outside the castle. So my father was in touch with the whole family, and we exchanged visits, and at the holidays they would come and we would go. So they were very warm, just like with the others. All the generations at the time had different relations with each other, and regardless of religion or religion, they were connected. Apart from that, did you go to Kourmanio with your father? Of course, and I remember as a child that I was there, when, with the cattle he had, from here and there he would put the big pots in which he had the vegetables. After he gave them to David and to George, he would give them away, and because I was young, he would put me in one of the pots, and we would go back to the house that was in the neighborhood, and after the war, back to Bostania. Apart from this friendship that your family had, did you play with Jews as a child? Of course, more so, not here in the area where we lived, in the neighborhood and in George's house, but especially in the period when my family was forced to stay in the castle, in a friendly house, during the bombings. As a result, I remember that I passed the first elementary school in the castle, as we go up, not from the big door, but from the other door, from here, to the left, in a big house, they had created a class of the first elementary school. There, I went to school, first elementary school, along with the children of the castle, both Jewish and Christian. As a result, when the class ended, of course, we would play outside, near the castle, and apart from that, when the siren would ring, we would run together, hand in hand, to hide inside the castle, from that door again, from that staircase. In the meantime, you stayed inside the castle? Inside the castle, because it was proven that when, with the bombings, we went down from the house, which was in the Big Alexander, in Bostan, and we hid either in the hut, where my father's animals were, or in other walls and trees, because there, where my father's cattle were, was the old serai of Bey Shey, who was the former owner of all the cattle, in the Paralimni, that area. As a result, it was proven that we could not protect ourselves. In the beginning, we went down to a large shed, which separated Bostan from the Bostan of the Leta brothers, and in fact, all the children were given, from a Jewish, I remember, they had given me, and put in my head, with the aim that if a bullet fell, it would slide from our halkom, from our halkom. As a result, my father found a friend of his, and he hosted us this time, inside the castle. How was it called? Thomas... How was it called? I will remember it in a moment. The road to his house was parallel to the road that is the Israeli... Synagogue? Synagogue. Have you been to the synagogue? Of course, I remember it as a dream when I was young, 5 or 6 years old, because I was 7 when the war started. We had gone to a Jewish wedding and as we were leaving, we went down this stairs from this door, the smaller one, not the big one, and there, the bride and groom, all the relatives took a photo at this point. I remember it as a dream. Did you appear in the photo? Yes, I remember. Another thing that I remember is that during the war, the families, especially this one, an orphanage, because she didn't have children, she stayed in the castle where there is a bridge in those houses, and there is still one. And she told her father that she would call Lenko, my mother Eleni, and she would bring the children. And I remember a visit, with food of course, but I remember the game she had given me, and I was more interested in the game than in eating with my family. Do you remember what the game was? I don't remember. I remember that it was something like a roller coaster, like a roller coaster, and I fell down with it. Was it common for the Jews of Ioannina to have such close social relations with Christians? Look, perhaps there were similar battles. Most of the time I think that this happened in the opposite places, in the shops. But at least I didn't feel that. And in fact, I remember that once it was heard that there was a woman against the Jews, and when I asked my father, he said to me, what nonsense are you talking about? Next time you won't discuss it. And who said that? What was that rumor? That there were some who wanted to mess with the Jews. Yes, but for what reason? Perhaps the professional, as I told you. But you personally didn't realize it. No. I came to ask you, you talked to me about the bombings. When did the bombings happen? Do you remember? Didn't you go to school? We had started school up here in Elisabetio, but with the bombings, and I don't know if the children continued here in this school where I was, but because we went to the house of Thomas Polka, who hosted us, I went to the first elementary school, I went to Kastro. When did things start to become more difficult for the city of Ioannina after the bombings? After the occupation. How did the occupation start? With the Italians, first of all, and for this reason we left the house of Thomas Polka, that is, during this period of war we stayed there, and we returned to our house, to the area of the gyrocomic. So then the father began to transform the big hut, because the walls were very old, the houses were also very good, and he turned the big hut into a house, with sheds, and as a result, in 1942, we moved into the big hut. Of course, this is where the occupation started. Of course, we didn't have so many problems with hunger and so on, because there were the vegetables of the shepherd, also two people who brought vegetables from our shepherd, and with their cattle they went to the villages and sold them, they brought vegetables to the mills and to the square where they cooked them for the visitors of the mill or everyone in the square. What is something that you saw at the beginning of the occupation as a child and that impressed you, that you saw with your own eyes, something that changed in the city? Look again, in general, as I told you, the period of the Italian occupation was not so difficult, that is, we went around comfortably, we changed the visits, David came to arrange what vegetables he wanted the next day, also because all these ruins from the old Serrae, there were trees, grass and so on, David had brought two sheep, which, together with our own sheep and the mare that our father had, he put in our hut. And so we didn't feel the occupation so much, where the SOS happened, it was with the Germans, the movement began, the blocs, they also caught these resistance prisoners, in the old Simea, the basements were full. Did you see such an occupation? Did you see with your own eyes some of these events that caused terror? I will not forget, as I write in my book, when hunger began, when we could no longer find wheat, the villagers outside, they no longer kept the wheat, the barley and so on, for their house, as a result, the father turned half of Bostani into a wheat field, and we secured the bread of the year, along with the fish, our lake was full of fish, my two older brothers, Kostas and Nikos, every night, in canisters, they tamed the anchovies with little dogs that they took out of a container that we had in Akrisos, and in the morning, we had a boat, and in the morning they collected a lot of fish, the mother decided which food she would make for us, and the others they threw them next to the well of the Bostani house, in a big barrel, it was from Pisa, clean water, they threw them there, and the neighbors, relatives and friends would come and take the fish, all that was there. Did your Jewish friends also come from Pestos, from Kurmanio? No, only Davis took the fish, because the others took advantage of the fish that the islanders took out, in the area and the scale that we are talking about, so the Jews had a connection with the islanders, but Davis, because he was a homemaker, as they used to say in old Ioannina, he also took the fish and halos sometimes. Also, what was amazing was that he was with the Germans, that's why I told you, there was a huge difference, the Italians would come and buy vegetables from our Bostani, and because they had seen Kostas, my brother, having a guitar and singing and so on, they would come and take the guitar and sing Italian songs and so on. And when, in fact, we remember, the greats would come, because I was the sitarist, the Italian would come and buy, and he would help in the therism to remember his village in Italy, but with the Germans and with the period of hunger, a bishop of the metropolis stayed in Caravatea, a friend of my father, because the bishops did not take money, the priests took advantage of the feasts that they did, that is, in the houses of the saints or in the cemetery. As a result, I asked my father to come and work in our Bostani. My father accepted him, they paid him normally, and he also bought vegetables for his family. Unfortunately, before we go to the unfortunately, he would come in the morning with a tarasso, with the Kalimafi, he would enter the house, and with the pants and the shirt, he would go where his father told him to dig, to clean the fields and so on. Unfortunately, it had become known that my brother Kostas, by boat, transported those who wanted to leave for Antarctica, and at night he brought them across to Durahan, where there is a monastery, and it seems that this had happened, and the Germans made a block in the morning, with voices, and the soldiers who were with the officer, saw the duke with a beard and hair, and because there was a well there, a water well, and we use it for the rooms and the facades, the two were thrown, they caught him and beat him. My father was shouting from here from the house, my mother had gone out and told the officer that he was not a worker, that he was not a partisan, they said, and they beat him. Finally, they brought him home, my mother went in and showed the tarasso and the Kalimafi, they did not do anything, they dragged him, my father made him shout, and finally a man appeared who cooperated with the Germans, and told the officer in a little German and a little Greek, that he was indeed a duke and not a partisan, and so he escaped. I remember the terror we received, I was holding on to my mother's scarf, she was crying, my father had completely lost her, finally they left, Kostas, the elder, shouting, the Russians, sorry for the expression, but unfortunately they were there, they did this to us, etc. And you understand that in that psychological state was also the duke. He said to my father, I will continue to dig, go home and rest, he gave him things for the house and for his family. We will stop here for a while, the story is revealing, we will stop for a while, and we will continue immediately after. Mr. Dimitris, you told us that this duke was betrayed by someone, and the Germans came and did this to him, and that this associate was with them. I would like to ask, were there other such incidents? Look, perhaps it was not specific to this person, it was simply for my family, because it had been revealed that my older brother was involved in the resistance in some way, because in the end it was proven that he was an anti-Soviet. And of course he had even transferred an Italian, because when the Germans blocked the Italians, they had put them in a camp, and one day, while there were Germans in front of us, they had come and camped there, and there my brother responded again, and he said that the Russians sent them to control our movement. Six German soldiers came with a battalion, they entered the house first, because at that time the houses were besieged, and the officers went to the larger houses, and the soldiers went to the smaller ones. And they entered, my mother explained to them that there were eight of us, that we were not fit, and so on. Fortunately, the youngest was from Austria, and he knew a little Greek, and he was a very good child. And he explained to the officer that they went and brought a rope, and between our house and the well in a large space, they put a large rope, and in fact I remember that they went and took sticks, as we say, from the fence, as they had cut them, and the father combed them and explained to them there, not that, and he went and gave them grass from the hut, and they rolled down, and from up there a bed to sleep. And of course they encountered great difficulty, because they went and stole the fruit from the trees, they took vegetables, even though they were going somewhere in a hole, it seems, and they brought food and ate at noon. So my brother insisted that they were sent separately, the ruffians, as we say, to spy on us. And what happened? While they had been locked from the door, because our house had two doors, one the main entrance and one from here, this one here, at that door from there, the Italian appeared, who was coming and selling the vegetables, he was coming and carrying the basket, in his dirty clothes, my mother opens the door and sees him. Where are you? They take him inside. Did you see him? Of course, they take him to the living room, he closes the curtains that we had on the windows, and it's good that he came from there, otherwise the Germans would have taken him. Now he was locked in the kitchen, he changed his clothes, my mother gave him clothes from my older brothers and from my father, they fried eggs with that, and Kostas says, he was up on the mountain, it was noon, the Germans, after they had eaten, they went for a swim, after they had eaten, they put him to sleep, so they took him from the other side of our house, they took him down to the lake, and on the boat that we had, my mother gave him bread and boiled eggs, and they put him in the boats that they had, and as I have very big photos, they left him there, so the night slowly went to the other side, and the pilot, fortunately, didn't have a moon, they took him to Durakhan, but he lost his senses, after the liberation he didn't show up, now what happened, they took him out, and you understand how we were waiting for my brother to come back, after that, and the most important thing, that the Germans were in front of us, they were in front of our house. I would like to ask you, because you mentioned that they had made a battlefield for the German soldiers, was that near your house? Yes, it was in the Ambelokipos, because it was a battlefield for the Italians first, and then for the Germans, so they were locked up there, and as a result they would be taken to different places, and he managed to escape, so he ended up asking us for help, because he was the closest partner, friend let's say, because they had become friends, we were singing with Kostas, he was helping here, in fact, many times he didn't pay, and he brought us food, pasta, and inside they had dry carrots and celery, and also cognac, I remember, in some bottles, round ones, with breadcrumbs on the outside, that is, there was this connection, and the only thing that the Italian thought about, was to come to our house, and in the end he escaped from the Germans, in the same way that Kostas did, my brother. I would like to ask you, during this time, that you are watching from the Germans, since they are like a shadow next to your house, did you still have contact with your Jewish friends? Very much, and that's where the thing is, when Davi came to the house, to sort out the vegetables for the next day, my father and my mother told him, Davi, go away, here the Germans catch all the Jews, from Germany, from other countries, etc. and from what we heard, we heard, because Kostas was mainly teaching them, and he came and told us, they caught the new Germans, the Jews, from the Tade area, etc. and Davi said, where are we going, Morenasio? I don't know what he said, go somewhere, to the villages, go to the villages, go to Athens, you are lost there, how can we leave our homes? Then he said, whatever the Germans want, we give them, what gold, what food, and in the meantime, Kostas insisted on the young people, and especially on his brother Ebi, who finally found the antarctic, he said, go away for the antarctic, come here, I will take you by boat, but he didn't say why, the president was explaining them, the president of that time of the Jews, that if children leave for the antarctic, they will kill your families, and no one was moving, they had this message, as if the kismet, as we say, was to be destroyed, and I remember, that he didn't say this only to David, to the speakers that were in the cafes, were you with them in these conversations? Of course, at home, of course, and you went to the cafes with your brother? No, not in the cafes, so how do you know these things? The father, first he gave the vegetables, then he went for a coffee, for a tsipouro, and we discussed it with the other Jews, not only with David, but with David I know it, because when he came to our house, and because there was so much connection between this family and ours, everyone insisted to find a way to leave, and let me tell you, two characteristics of the connection that we had with this family, with hunger now, there was no food, there was no rice, there was no sugar, and no coffee. My mother, I remember, she used to make coffee, and the coffee was made with this. They had the griller, they cut it, and the coffee was now with raisins and raisins. So, one afternoon, David came to talk to the father, and as soon as we finished eating, he heard my mother say to my mother, Vrelenko told her, there is no rice, as they used to say in Ioannina, to make stuffed, because my mother had made stuffed with tomatoes and peppers, and instead of rice, she threw dill, because, since we had the griller, they had the hands that we used to say, they had bought them, and they cut the griller, and with this they made drachana, and with this ground griller, they made stuffed. So, David says, what does my mother say? David says, my mother has thrown, she says, she doesn't know what time it is, don't you understand, mother, that we are in captivity, and these things don't exist. So, in the afternoon, David appears, and he says, mother, open the table, give me a sack of rice, another sack with sugar, which I remember, I have this left, it was in cubes, the sugar, not the liquid that we had, and he says, now I will say to Lenkuts, mother, to make stuffed with rice. And, another evidence of the connection of this family with ours, was, when, between Hellas and Edes, Hellas had come all the way to St. Nicholas, from Perama and a little further. And here in Ioannina, was Edes. As a result, one morning, a milkman, from Perama, who brought the milk and he was selling it in our neighborhood, came to Bostani, and he knew the father, because he was coming from Perama, the upper Bostani, where we put the sieve, he was coming, and he was selling it all, and we did not limit ourselves only with the sieve, or only with the sieve that we made in the small areas. So he says to him, here, come over there, to St. Nicholas, one of them, asks you, me, says the father, he did not tell me who he is, says my mother, do not go, they will see me, for the Germans, not for the Germans, for the Edesites, the Germans had left, it was after the liberation. So my mother says, do not go, to see if he is one of my successors, because he had left, it was after the liberation. So he goes, and the father comes back, almost crying, do you know who he is? Who is Anastatothika Meoni? Emi, the brother of Davi. And he said to me, he wants clothes, because he is with these clothes, he left, when they were going up to Michikeli, at a stop where they made the trucks, which we will describe later, because, all the Jews caught them, and they went with the trucks, and he made it, and went to the mountain. So, I found in Greece, and happily, that Emi now lives, and he gave him clothes, and from the father, from Kostas, from Nikos, and he wanted shoes, because they had opened it for him. And shoes, which the elders used, which we had in Bostani. And of course, he came back, and opened his shop, and we continued to have the communications, with Emi. I want to say, that this connection existed, maybe with the other families, maybe with the other families, more, relaxed, but more with this family, very big. I want to go back a little. You described to me, how David was coming, almost on a daily basis, there, without fear, without anything. When did these visits stop? What changed for the Jews? The visits, simply, each one had been imprisoned, in his cell, but we did not stop, we did not stop, to have the communication. Simply, the tables, the plates, in some way, because it was continuous from the Germans. The blocks, the blackout, they cut off our power. You could no longer move. The only one who came, was David, who came to make arrangements with the father for the vegetables. The father went to the vegetables, with Haidur, and there, he met with the others, and he went to the house, and sometimes the mother, went to her, mainly to Esther, because, they did not have children, and the connection of Esther with my mother had come more closely. Do you understand? And the amazing thing, was that, that day, the wait, that David came to our house, to make arrangements with the father, for the vegetables for the 25th of March, he said, I will take the sheep, because in the garden, the grass has grown, at least they eat it. What happened to the block? What happened to the block? What do you mean? The Germans intervened, of course, they said, later we learned, that the manager came with a hydroplane, they came, they had appeared, not so much in Istanbul, with those tanks, Did you see them? Of course. Where did you see them? In the neighborhood, it was the fear, the fear and the fear, and for us, the children. And they say, they said later, that they were the ones who gathered the Jews, and not those, who were already in Ioannina, and they took the gold, they took the money, they took the food, they took the best houses of the Jews. How did they separate the Jews from the non-Jews in Ioannina? They put the Christian houses in the castle, they forced them and they put a cross outside, at the door. How did they force them? They passed, the garrison, the Greek garrison, who cooperated with the Germans. Now, maybe they weren't, but since they were the workers, but some of them were. Did you see them? I only saw the cross that had entered the house of Thomas Polka, because we didn't stop having communication with this family, since they hosted us for a whole year. Do you understand? So, after that, I think they had taken a list of all the Jews. Who gave them the list? I don't know, maybe the president. I said, after that, and then his father said in front of all of us, don't have faith, leave, not that one, or that one, or that one. And they stayed in sleep, as we say, and they caught them. And while on March 25, with a cold, a snowy water, the mother, mainly, told us that it is a double celebration of evangelism and this and that, and so on. And while we were preparing in some way to go to the church someone came there and said that and that. They caught the Jews and took them down to the pier. So, we were all resurrected. The father with his son, the eldest, left to go to the center of the city to learn the commandments that we say. The mother started crying and we all went out and no one went in, not even the church, we went out to the street of the great Alexander, to the sidewalk, and other neighborhoods, and so on. Meanwhile, Kostas came back and said that the block could not go there, because it was almost at Saint Nicholas of Agora and up here, a little lower from Gialikafenai, as we say. So, you could not suffer more, just the fact that they were caught. And there were discussions in front of the neighborhood with us, the children, with the neighbors. We had lost the father, I did not know where he is. Did you see anything from where you were? Where we were, which is the house, the rented house, and from there we went to Bostani, we only saw the depth of the neighborhood. So, from there we realized, from where we lived, we realized the cars were approaching the neighborhood. They had started to leave? Yes, to leave. It was 10 o'clock and it was snowing, in front there was a car with German soldiers, and trucks were following, which were covered with snow, and everything else was completely covered, as we say. And now they started to pass in front of the trucks. How close were you? Completely. How can I tell you? Because at that time there was no road. Now the road was widened. How is the road of Josef Ligya, as if we were on the sidewalk, in front of the office, and the trucks were passing in front of us. 10 meters? A little less. But, almost, here on the sidewalk the cars were passing. Did you have contact with the Jews who were in the trucks? Of course, that's why I told you that it was direct communication. I remember the others were scared. Most of them were shouting with their hands not to be lost. It was terrible. And, after 5-6 trucks passed, in one of them from an iron that the truck had there, Davis was holding with his hand and he was looking to the side where we were, because it was visible that at this point there were no houses. There was a house, where the children and the neighbors were sitting. And he was looking in front of the tables to see our shepherd. So, at that moment, while he was holding with his hand, his wife and children were in front of him. John, my brother who was next to me, said to me, Davis, he was looking at us and said, that the money that I owe him, I have it on my shoulder and to take both sheep from the garden. Davis, and in the meantime, he continued to greet us until he was lost in the turn from the crossroads where the house of St. George is. We were armed, my mother was crying next to me and my older sister. Now, where can we find my father? And, while I was going to find him, I found him in the narrow alley opposite the house where we lived, in a stone, in an island house, because it was all a poor house there. And he was sitting there, and he said this and that. And there I saw him, crying. And he says, they are lost, and I will go to get the money. And then, the money was lost, and the sheep were lost. Who will take them? What happened? What happened, after the Jews left? Many things were checked, that most of the wealth was taken by the Germans. Many were taken by the collaborators. The point is that the people were lost. It was not so much that the revival of all, and especially my house, and especially my father, had become, I confess, I had never seen him cry. And we, the children, went down to the pier, and we went to the edge of the lake, and we watched the trucks that were going up the road and they were going to Larissa. So, there, we were all silent, all the children. One, why did they come out? They all left, and there I sat, and I still had that shiver, which I felt more, to see my mother with my sister crying, and all the neighbors, my father from Korythoma, and I felt that my heart would break. And after 50 years, I lived and wrote in my book this whole story. I would like to ask you, with the liberation, did you find some of your friends, your acquaintances, the Jews? Did anyone come back, except for Ebi, whom you described to us? Yes, and another couple, and I remember when with the Association of Old Generation, which we had already done, with the excursions, three couples would come, Ebi with his wife, he was married, and he had opened a shop in Giuseppe Ligia, on the left, in the corner, and two other couples. Do you remember names? I don't remember names, I only remember the characteristic, that one of the three couples, when in this group that was gathered, a friend of my brother, Tamiakou, came with his wife, so, oh, Giorgo, as they called him, from the village of Zagorio, and they hugged each other, they kissed, I said, what? How do you know each other? He said, since we had him at home, we had them at home, in the village. And from this I draw the conclusion, that they had to leave, when the mother and the father, left for the village, to leave for the city. When I met Mrs. Nachman, she saw my book in Athens, and she called me, and we connected and presented her book to Nachman, then I thought that when the father was saying, I said to Nachman, then happiness changed and it became Nachman. And it turned out that it was the nuns of happiness, who had shops in independence, and their brother, the father of happiness, was constantly in Athens, who supplied the shops in Ioannina with supplies from Athens. And it turned out, as Mrs. Nachman told me later, that he sent them a letter to leave and go to Athens, and the nuns did not accept it. And from this I conclude that it was the father who wanted them to leave. And it turned out that the Nachman family escaped, with the spread that happened, that is, the couple stayed elsewhere, happiness in another house, and her brother in another house, as described in her book. And she was following these Christians, so that the Germans would not learn and arrest them. Was there any impact on the life of the family or on your brother's reaction to Kosta? Unfortunately, yes. Because they put him in prison and it was proven that when my other brother, Nikos, was appointed as a prosecutor in the municipality, it was proven that they had a bag and they did not give him a certificate of social service. My brother, Giannis, who had completed his studies, probably, at the Gymnasium and completed his gymnasium, when he went as a soldier, he was sent as an officer in Goryndo, he was deprived of being an officer and they put him in prison for unknown reasons. Because Giannis was in his last year of studies, I had finished my studies and because I was a good student, I wanted to study medicine because my mother was sick. And a military doctor, a friend of Kostas, said to him, since Dimitris is good, why don't you go to the military or medical school? So, both are good and in America they sent me with education and so on. In the end, I moved on, I passed the committees, some other tests and so on, I went to the school in Thessaloniki, I passed the exam, there were 25 seats, there were about 180 people, I passed the exam, I passed the exam, I passed the exam, I passed the exam, I passed the exam, I passed the exam, and when I returned home, which was a friendly house, I asked what happened to Dimitris, they told me that my parents had established Dimitris. I said I had done well in chemistry, but the next day when I went, I saw a drop. I was upset, I returned to Ioannina, an uncle of mine who helped us because he was in a way a leader and he helped. When they were punishing Kostas, he went to the manager and said, what is going on? The child is in the bus, he works, why did he go out? He went to the square, they went for a meeting and the man who had told him not to go out again, Kostas, what are you saying? Anyway, and my uncle says to me, did you write well, Dimitris? I wrote well, he says, I will ask. And he wrote to a lawyer in Thessaloniki and one day I went to a store to help them, I went because I didn't have a job, I was waiting for the soldier to go. And he showed me a telegram and said, if you have any questions, please contact me. And after 3-4 days I received a letter that the social care was delayed and they couldn't cut me under the supervision of the lawyers, that's why the only way was to say that I didn't write well. And since then I waited, I went to the soldier, they put me as a witness, and it turned out that the social care committee where we spent that time, the lawyer and so on, had me as a witness. And this was proven when I was presented in Kerkira and then in the school in Athens. And because I was the first to go, the teacher told me where I should go. And I told this to Yannana, because she was my mother. And already while I was in the education center in Kerkira, my father died, and they didn't let me come. I didn't see him. And I came to Yannana, here where in Talithari was the military base. Then it became a tourist theater. A well-known officer of Kosta tells him that, you know, they have the little sign. But I will try, he says, to identify him. And it was then that the events of Cyprus with the English took place. And I sat and wrote something and unfortunately I did the nonsense that I later lost. And when they went to the commander of the battalion, he called me and said, my son, you are amazing. He told me to write a few words, but you, this is something amazing. And they put me and I said it to the whole battalion, and my legs were shaking because it was the first time that I appeared to so many people. And when after there I was demoted and the commander told me when I was in Stilia on the Borgana, he had taken permission and gave me the certificate and he says, here is the certificate and I look at it and it is rejected due to social considerations. That's all. The fact is that I did not study, I gave exams, I became a director at the Municipal Hospital of Ioannina, I started as a manager, I became a director, they closed the Municipal Hospital, then I was transferred together with the others to the Chantikosta Hospital as a deputy director, then as a director and I was appointed. These are stories that when you live them, they remain inexplicably. We will stop for a while. Think if you want to add something from your experiences and I will talk a little with the colleagues if they want to ask something. Yes. Three, two, one, let's go. Mr. Karaki, I would like to clarify some points if you really have answers for these. First of all, there was a donor who came and searched your house and because of him your brother was imprisoned and so on. Do you know the name of this donor? Did you ever learn how it was called? He was almost a neighbor. Kostas, his youngest son. He had two women who later said that he married one of them and it was circulating that he was also exiled to the Germans. Unfortunately, he lived, he was not convicted. He was also deported to the hospital and I remember when he brought a sick old woman to the municipal hospital, he came and told me I know you Mr. Karaki. I said, I know you from the French. I mean, I want to say with this that those who dealt with the Germans were comfortable except for those who said that some left with them. That is, there were many more than one and two who worked together. Of course, I don't think that he was the only one. He was in our neighborhood in some way. In your story, where Davi talks to the father who and your brother Kostas go to the mountain, you mention what Davi heard in his community. Once you told us about Rabino. Once you told us about the president. Who were they? Do you know their names? Have you ever seen them? I don't remember the name of the president. I don't know. I just saw him as a child when I went down there. But he assured them and he kept that Davi and as the father said and the others that with all that we give to the Germans, they will not interfere at all. Who did that? The president or Rabino? The president. Because you told us that Davi also mentioned Rabino. And when your father said don't listen to what they say, to whom was your father referring? That some Christian youths had a conflict with the Jews and that something could happen with the Jews from the Germans, as it happens in other cities. Especially the climax and the pressure that was on Davi was when the Germans captured Thessaloniki. And your father said in the name of God. What else do you expect? That here in Thessaloniki they gathered and you are still sitting? No. Did you hear that? The president said that it would not be affected. And that's why I told you that more they had calmed down that the Germans who were in Ioannina would not be affected. And those days they brought others with those crutches and they walked and they turned around in the streets and then the plane came with the head that showed that it was the president I mean that the pressure was from the Christians and especially from my own people. Now, if there were people who were against this, it proves that the most important thing is that they had to enter... that's why I told you that they were leading to the destruction. That's what I wrote in my book. That is, they had calmed down. But when they saw that they put crosses in the crutches of the Christians they had to put more thought into it. But they had stuck to that. And especially, more that I heard was with David because he came every day or his family came. Especially in the summers they came because it was the coolness of the lake the environment of the garden. Then it wasn't just a garden with vegetables. It was the house. It was the garden. It was overgrown with leaves, trees, flowers. So you had social relations with his family. Of course. How old were his children? They were young. Were they younger than you? No, they were older than me. Did you play with them? When they came to Bostan, yes. Do you remember their names? No. His wife? No. David and Ebi were left. Because they came more often to the house. I would like to ask you how fast did the trucks go that you saw from afar? No, slowly. Slowly? And how many hours did you watch them? When did you leave from there? You told me that 4-5 trucks passed and then it was the truck with David. Yes, and they continued to pass. Did you see them? Of course. We didn't leave. I just left from the opening of the play I told you about where David was trying to see Bostan, to see his father. And I left and came back because I told this to my father. I was shocked. I left him and he went to Bostan crying. And I came back here with the other kids, the neighbors and we continued to watch this one. And others were shouting to remind us. Others were gathered and from the cold, to throw the snow water. And the Christians who were watching from below, what did they tell them when the Jews were saying to remind us? Yes, you will come back and you will be sad. Something like that. But why? No one expected that they would be executed. We thought that they were just caught like they did with the Italians. That they should work etc. But this thing that ended up was terrible. Is there anything else that you remember and you want to tell us before we close the interview? What else can I tell you? That the unbelievable things that we told them to leave. You will tell me what Davis was saying where to go. It is our home. It is our things. It is our family. They did not think that they had been silenced by the president. As a result they were destroyed. What else can I say? One last question. Have you ever seen Rabino? No. Do you remember who he was? No. Thank you very much for this interview. Your testimony is very valuable. We will finish today. Thank you very much for having us again. I think that all of us in this group thank you very much. Thank you. It was shocking the events that have shaken me in the most serious way. And think about it I was a small child because I was already 10 years old. I was 40 years old. You were from 33 to 43. Yes, of course. Do you understand? Yes, of course.